Treasury of Pony Stories - "Jennings, Linda" (Kingfisher Books Ltd: London, 1996)
First published in 1996, a collection of sixteen pony stories by such authors as Christine Pullein-Thompson and Adele Geras. Includes folktales from America, France, Scotland and a Greek legend. Illustrated in black and white by Anthony Lewis.
Keywords: Horses Juvenile fiction